Life support and euthanasia, a perspective on Shaw's new perspective. Issue 2 (28th October 2010) - Busch, Jacob; Rodogno, Raffaele
Abstract : It has recently been suggested by Shaw (2007) that the distinction between voluntary active euthanasia, such as giving a patient a lethal overdose with the intention of ending that patient's life, and voluntary passive euthanasia, such as removing a patient from a ventilator, is much less obvious than is commonly acknowledged in the literature. This is argued by suggesting a new perspective that more accurately reflects the moral features of end-of-life situations. The argument is simply that if we consider the body of a mentally competent patient who wants to die, a kind of 'unwarranted' life support, then the distinction collapses. We argue that all Shaw has provided is a perspective that makes the conclusion that there is little distinction between voluntary active euthanasia and voluntary passive euthanasia only seemingly more palatable. In doing so he has yet to convince us that this perspective is superior to other perspectives and thus more accurately reflects the moral features of the situations pertaining to this issue.